The Role of Evolution in Shaping Ecological Networks - Segar, Simon T; Fayle, Tom M; Srivastava, Diane S; Lewinsohn, Thomas M; Lewis, Owen T; Novotny, Vojtech; Kitching, Roger L; Maunsell, Sarah C (Trends in ecology & evolution, 2020)
The structure of ecological networks reflects the evolutionary history of their biotic components, and their dynamics are strongly driven by ecoevolutionary processes. Here, we present an appraisal of recent relevant research, in which the pervasive role of evolution within ecological networks is manifest. Although evolutionary processes are most evident at macroevolutionary scales, they are also important drivers of local network structure and dynamics. We propose components of a blueprint for further research, emphasising process-based models, experimental evolution, and phenotypic variation, across a range of distinct spatial and temporal scales. Evolutionary dimensions are required to advance our understanding of foundational properties of community assembly and to enhance our capability of predicting how networks will respond to impending changes.
Keywords: metacommunity; ecophylogenetics; phylogeny; Biological Evolution; ecoevolution; adaptive network; microevolution; biologická evoluce; ekosystém; Ecosystem